2016
DOI: 10.1186/s13229-016-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Atypical lateralization of motor circuit functional connectivity in children with autism is associated with motor deficits

Abstract: BackgroundAtypical lateralization of language-related functions has been repeatedly found in individuals with autism spectrum conditions (ASC). Few studies have, however, investigated deviations from typically occurring asymmetry of other lateralized cognitive and behavioural domains. Motor deficits are among the earliest and most prominent symptoms in individuals with ASC and precede core social and communicative symptoms.MethodsHere, we investigate whether motor circuit connectivity is (1) atypically lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
73
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 141 publications
11
73
2
1
Order By: Relevance
“…The left-lateralized hypoactivation seen in the ASD group in the present study was consistent with two resting-state functional connectivity studies that reported atypical right-hemisphere lateralization of motor circuit connectivity in ASD [Cardinale, Shih, Fishman, Ford, & Muller, 2013;Floris et al, 2016]. Consequently, performing the task of anticipating when the basketball would bounce based on visual motion information may have been readily processed by left corticobasal circuits in the TD group.…”
Section: Discussionsupporting
confidence: 90%
“…The left-lateralized hypoactivation seen in the ASD group in the present study was consistent with two resting-state functional connectivity studies that reported atypical right-hemisphere lateralization of motor circuit connectivity in ASD [Cardinale, Shih, Fishman, Ford, & Muller, 2013;Floris et al, 2016]. Consequently, performing the task of anticipating when the basketball would bounce based on visual motion information may have been readily processed by left corticobasal circuits in the TD group.…”
Section: Discussionsupporting
confidence: 90%
“…They found abnormalities in the connections between the motor and sensory hand regions which was associated with poorer performance in the pegboard test. Interestingly, the differences in correlations between control and autistic groups suggested a lack of the typical left dominance for motor performance in the autistic group, and that this reduced asymmetry was related to poorer performance, as also found by Floris et al (2016).…”
Section: The Neuroanatomical Correlates Of Movement Impairmentmentioning
confidence: 82%
“…Precisely 49 studies comparing ASC and typically-developing (TD) control groups answer this question in the affirmative. The more methodologically rigorous studies, those which a) either matched for chronological and/or mental age and/or IQ or b) controlled for these in their analyses, and c) had more sizeable groups (>30 per group) demonstrate that motor impairments occur more often than might be expected in TD children (AbuDahab, Skidmore, Holm, Rogers, & Minshew, 2013;Ament et al, 2015;Dewey, Cantell, & Crawford, 2007;Dowell, Mahone, & Mostofsky, 2009;Duffield et al, 2013;Dziuk et al, 2007;Floris et al, 2016;Sumner, Leonard, & Hill, 2016;Travers et al, 2015Travers et al, , 2016. A meta-analysis of 41 studies confirmed that, despite substantial variation, effect sizes are large with TD participants significantly outperforming individuals with autism in motor coordination, arm movements, gait and postural stability (Fournier, Hass, Naik, Lodha, & Cauraugh, 2010), and that these effects did not seem affected by publication bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents and young adults with high‐functioning ASD were found to have atypical lateralization of diffusion indexes in the Cingulate, AF, and Uncinate Fasciculus (UF) [Fletcher et al, ; Knaus et al, ; Lo et al, ], in the Superior Temporal Gyrus (STG) [Lange et al, ], in the pathways involving the fusiform [Conturo et al, ], in the temporal lobe (parahippocampal gyrus, STG, sagittal stratum) [Peterson, Mahajan, Crocetti, Mejia, & Mostofsky, ] or within the corpus callosum [Floris et al, ]. An atypical laterality pattern was also reported in functional magnetic resonance imaging (MRI) studies showing altered asymmetry in brain representation of language‐related networks [Lindell & Hudry, ] or even in motor circuits [Floris, Barber, Nebel, & Mostofsky, ]. Emerging evidence suggests that an atypical lateralization is already present in younger children.…”
Section: Introductionmentioning
confidence: 99%